Translation Stress Regulates Ribosome Synthesis and Cell Proliferation - Vadivel Gnanasundram, Sivakumar; Fåhraeus, Robin (International journal of molecular sciences, 2018)
Ribosome and protein synthesis are major metabolic events that control cellular growth and proliferation. Impairment in ribosome biogenesis pathways and mRNA translation is associated with pathologies such as cancer and developmental disorders. Processes that control global protein synthesis are tightly regulated at different levels by numerous factors and linked with multiple cellular signaling pathways. Several of these merge on the growth promoting factor c-Myc, which induces ribosome biogenesis by stimulating Pol I, Pol II, and Pol III transcription. However, how cells sense and respond to mRNA translation stress is not well understood. It was more recently shown that mRNA translation stress activates c-Myc, through a specific induction of E2F1 synthesis via a PI3Kδ-dependent pathway. This review focuses on how this novel feedback pathway stimulates cellular growth and proliferation pathways to synchronize protein synthesis with ribosome biogenesis. It also describes for the first time the oncogenic activity of the mRNA, and not the encoded protein.
Keywords: Cell Cycle; proteosyntéza; ribosome biogenesis; Disease Susceptibility; lidé; mRNA translation stress; signální transdukce; Ribosomes; Animals; Signal Transduction; Humans; cell signaling pathway; buněčný cyklus; ribozomy; fyziologický stres; cell cycle; Cell Proliferation; zvířata; náchylnost k nemoci; Protein Biosynthesis; Neoplasms; oncogene; nádory; Stress, Physiological; messenger RNA; RNA, Messenger; proliferace buněk